Analysis of Non-Equivalent Terms for the Concept of Education in English and Uzbek (International Journal of Scientific Trends, 2024)
The article presents various definitions of the concept of paremia , and through a comparative approach to the concept of "Education", the culture, worldview, and customs of the languages being compared are also interpreted along with the theory of the concept. At the same time, the linguistic features of the concept of "education" in English and Uzbek are analyzed based on lexicological and grammatical levels.